Filsafat Politik Arendtian: Korespondensinya terhadap Pancasila dan UUD NRI 1945 - Muhammad Imadudin (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2021)
Arendt is known as both a political theorist and a political philosopher. Scholars discuss her ideas, and their correspondence to contemporary political situations; in Indonesia and elsewhere. Arendtian political philosophy rejects violence, group hegemony and domination, also, homogenization and uniformization of geopolitical entities. Meanwhile, the founding fathers of Indonesia have established Pancasila as the worldview and the philosophical basic of the State. To complement the established basic of state, the Preamble of the 1945 State Constitution of the Republic of Indonesia is enacted, contains the vision and mission (goals) of the independence of the Nation. This paper explores the correspondence between Arendtian political philosophy with Pancasila and the 1945 State Constitution of the Republic of Indonesia, as well as its contemporary interpretations. I use comparative approach in witing this paper. It compares Arendtian political philosophy and Pancasila, to find correspondence and correlation between the two. Significance of of this paper to find out the correspondence between the two, in order to develop studies on Pancasila and the 1945 State Constitution of the Republic of Indonesia.